(untitled) (Progressive Agriculture, 2017)
The organophosphorus insecticide, diazinon that is widely used in agricultural field and private industrial premises to control pests, easily accumulates in aquatic ecosystems and exerts toxic effects on aquatic animals. The study aimed to evaluate the acute toxicity (LC50) of diazinon on Glossogobius giuris and histopathological alterations of its gonads, liver and kidney due to the effect of this insecticide. G. giuris were exposed to different concentrations of diazinon ranging from 0.00025 ppm to 2.048 ppm with parallel untreated control. At the doses of 0.0005 ppm, 0.001 ppm, 0.002 ppm, and 0.004 ppm 40%, 50%, 70%, and 90% mortality of G. giuris were observed within 96 hrs, respectively, whereas, 100% mortality was observed at doses above 0.008 ppm. Based on probit analysis, the LC50 value of diazinon for 96 hrs of exposure on G. giuris was found as 0.001 ppm. During the exposure trial several behavioral alterations including restlessness, sudden and quick movements, loss of equilibrium, increased opercular activities and paralysis were observed in the fish. The histopathological changes observed in the tissues of G. giuris indicate that sub lethal concentration as well as higher concentration caused moderate to severe alterations in the liver, kidney as well as gonads. Kidney was found to be the most seriously affected organ compared to gonads and liver. Major histopathological changes like fragmentation of testis and ovary with ruptured wall, karyolysis, hypertrophy, pyknosis and degenerative changes such as necrosis of tubular and haematopoietic cells of kidney, necrotic hepatocytes, pyknosis, hypertrophy, haemorrhage and vacuolation were observed in the liver cells. The present study demonstrated that diazinon is highly toxic especially to G. giuris and thus, indiscriminate use of this insecticide in the agriculture and industrial sectors should be strictly controlled. Progressive Agriculture 27 (4): 530-538, 2016